Microwave line of sight link engineering - Angueira, Pablo; Romo, Juan Antonio (Hoboken, New Jersey : Wiley, 2012)
BA comprehensive guide to the design, implementation, and operation of line of sight microwave link systems/b/ The microwave Line of Sight (LOS) transport network of any cellular operator requires at least as much planning effort as the cellular infrastructure itself. The knowledge behind this design has been kept private by most companies and has not been easy to find. iMicrowave Line of Sight Link Engineering/i solves this dilemma. It provides the latest revisions to ITU reports and recommendations, which are not only key to successful design but have changed dramatically in recent years. These include the methodologies related to quality criteria, which the authors address and explain in depth./ Combining relevant theory with practical recommendations for such critical planning decisions as frequency band selection, radio channel arrangements, site selection, antenna installation, and equipment choice, this one-stop primer:/ ulliDescribes the procedure for designing a frequency plan and a channel arrangement structure according to ITU current standards, illustrated with specific application examples/liliOffers analytical examples that illustrate the specifics of calculations and provide order of magnitude for parameters and design factors/liliPresents case studies that describe real-life projects, putting together the puzzle pieces necessary when facing a real design created from scratch/li/ul iMicrowave Line of Sight Link Engineering/i is an indispensable resource for radio engineers who need to understand international standards associated with LOS microwave links. It is also extremely valuable for students approaching the topic for the first time.
Includes index.
Keywords: TECHNOLOGY